Corundum Refractory Material in Alumina-Binder Resistant to High-Temperature Deformation - Pletnev P. M. Petr Michailovich; Pogrebenkov V. M. Valery Matveevich; Vereshchagin (Vereschagin, Vereshagin) V. I. Vladimir Ivanovich; Tyulkin D. S. Dmitry Sergeevich (2018, 2018)
Title screen